Pelatihan Kegiatan Fun English Untuk Meningkatkan Kemampuan Speaking Para Santri Asrama Putri Pondok Pesantren Sunan Drajat - Nanda Lahita; Shohiyah Shobaha (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This community service (PKM) activity aims to improve students’ speaking skill and to foster a full awareness of the importance of using English in their daily lives at the female dormitory of the Sunan Drajat Islamic Boarding School. English is an international language studied at almost all levels of education, both formal and informal. This clearly plays a crucial role in communication, especially in the globalization era now. Aware of the importance of English, the Sunan Drajat Islamic Boarding School has implemented an English Area. For the English Area to run effectively, students' English language skill and competencies are required. Therefore, the morning class and the upgrading class are held to support the students' English learning. Although the English classes are held, students' awareness of English is still low. It is be a challenge itself to habituate students to speak English in their daily lives. Therefore, this community service (PKM) activity was held using several instruments; observation, interview, and documentation to determine the condition of English learning process and the students’ English skill. Then, coaching and training were carried out on the application of Fun English strategy for the tutors of female dormitory at the Sunan Drajat Islamic Boarding School. The Fun English strategy implemented includes; the application of flashcards, word chains & charades in English learning. This Fun English strategy aims to motivate the students and make them interested in learning English. It is proven that after the Fun English activity was held, the students' vocabulary mastery and speaking skills increased and they began to habituate themselves to speak English with correct & appropriate sentence structure in their daily activities.